Primary systemic vasculitis with severeα1-antitrypsin deficiency revisited. (May 2014) - Mohammad, A; Segelmark, M
<x xml:space="preserve">Abstract</x> Objectives: To study the clinical characteristics and epidemiology of the combination of primary systemic vasculitis (PSV) and severe alpha-1 antitrypsin (α1-AT) deficiency. Method: Patients with PSV [granulomatosis with polyangiitis (GPA) (Wegener's), microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis (EGPA) (Churg-Strauss), and polyarteritis nodosa] were identified through diagnosis registries and serological databases. Clinical and laboratory data, including the presence of severe α1-AT deficiency, were collected from the time of diagnosis. During follow-up, data on relapses and permanent organ damage were collected. Using the county of Skåne as the denominator population, we estimated the annual incidence rate and point prevalence of PSV in people with severe α1-AT deficiency. Results: Five patients (three women, median age 49 years) with PSV diagnosed between 1996 and 2008 were found to have α1-AT deficiency, all of them carrying the protease inhibitor ZZ (PiZZ) phenotype. During follow-up (median time 166 months, range 53–208), four patients experienced a total of 13 relapses. The median Vasculitis Damage Index (VDI) score for all patients was 3 (range 1–4) at year 1, and 7 (range 3–9) at the last follow-up. The incidence rate of PSV among PiZZ carriers was estimated to be 397/million [95% confidence interval (CI) 8–787]. The point prevalence on 1 January 2013 was estimated to be 4689/million (95% CI 94–9285). Conclusions: In this study both the incidence and prevalence of PSV were elevated nearly 10-fold for individuals with severe α1-AT deficiency compared with the general population. Combined with previous publications, this indicates a dose–response relationship for the genetic risk and suggests a causal relationship between the PiZ allele and vasculitis.